The Study of Insect Population - S. Sastrodihardjo; Adianto Adianto; Liem Khian Kioe (Institute for Research and Community Services (LPPM) ITB, 1969)
Abstract. Insect population has been subjected to several environmental factors. Included within this environmental category are the type of food, the place to live in, the climatic conditions, etc. This study has been leading to seek of key factor in the regulation of several insect populations. First, the population of APHIS GOSSYPII on cotton plants. It is apparent that the physiological condition of the leaves is the primary regulating factor. Secondly, the size of the population depends also on the food from which the energy came. Corn meal supported large population of TRIBOLIUM CASTANEUM, followed by soy meal, rice meal, and katjang idjo (green bean) meal. However corn meal plus rice meal plus milk powder (45:45 :10), supported the largest size of TRIBOLIUM population; the fluctuation occurred on the level of 300 individuals per 10 grm medium. Furthermore, BRUCHUS PHASEOLI (another insect pest) refused to oviposit on katjang idjo meal, but thrived on katjang idjo bean. This behavioural factor is believed to be the primary regulating factor. The quality of the bean and also the thickness of the skin may further regulate the population. Finally the climatic factor effected the behavior as well as the life-cycle of several insects caught in the vicinity of ITB campus. Ichtisar. Populasi serangga selalu terkena oleh pengaruh factor keliling. Termasuk didalam category faktor keliling ini adalah djenis makanan, tempat untuk hidup, keadaan iklim tsb. Studi ini telah mengarah kepada pentjaharian